Polypyrrole/zeolite composite – A nanoadsorbent for reactive dyes removal from synthetic solution. (January 2022) - Senguttuvan, S.; Janaki, V.; Senthilkumar, P.; Kamala-Kannan, S.
Abstract: Synthetic dyes are among the common pollutants in the ecosystem. In the present study, polypyrrole/zeolite (PPy/Ze) nanocomposite was prepared and subsequently assessed for the removal of Reactive blue (RB) and Reactive red (RR) from synthetic solution. The polymeric PPy/Ze composite was synthesized by chemical oxidation of pyrrole in the presence of zeolite. Electron microscopic images (transmission and scanning) indicate that PPy/Ze nanocomposite was spherical in shape with an average size of 40–80 nm. The characteristic pyrrole and zeolite Fourier transform infrared spectrum peaks (1542 cm −1, 1463 cm −1, 1156 cm −1, 1054 cm −1, 879 cm −1 and 756 cm −1 ) in the nanocomposite confirmed zeolite integration with polypyrrole. Experimental variables such as PPy/Ze nanocomposite dose, initial RB and RR concentration, reaction temperature and pH were optimized. The PPy/Ze nanocomposite adsorbed 86.2% of RB and 88.3% of RR from synthetic solution at optimal conditions (pH 9, initial RR or RB concentration, 75 mg/l; PPy/Ze dose, 1.8 g/l; and temperature, 50 °C). Freundlich isotherm model and pseudo-second-order kinetics showed better fit for both RB and RR removal from synthetic solution. X-ray diffractogram confirmed the amorphous nature of PPy/Ze nanocomposite and that it was not altered even after dye adsorption. Adsorption–desorption studies showed that the composite has satisfactory adsorption potential for four cycles. The results show that the PPy/Ze nanocomposite could be used for the removal of dyes from wastewaters. Graphical abstract: Image 1 Highlights: Polymeric PPy/Ze composite was synthesized by oxidation of pyrrole with zeolite. Integration of pyrrole and zeolite was confirmed by FTIR studies. PPy/Ze nanocomposite removed 86.2% of Reactive blue and 88.3% of Reactive red. Hydrogen bonding and electrostatic interactions are responsible for dyes adsorption.